Characterization and isolation of oil palm lipid transfer protein (EgLTP) gene putatively responsible for defense against fungal infection (Ganoderma boninense) during basal stem rot infection - Al-Obaidi, J.R.; Mohd-Yusuf, Y.; Othman, R.Y. (Academic Journals, 2013)
Lipid transfer protein (LTP) is essential for the activation of plant defence responses. One of the LTP roles is to involve in the defence against fungal infection in plant cell. In this study, our aim was to isolate the LTP gene from oil palm based on LTP gene sequence from other monocot gene databases and to get insight to the function of this gene during fungal-plant infection. Four model plants were selected which are Oryza sativa, Zea mays, Triticum aestivum and Lilium longiflorum. Five degenerate primer pair combinations for conserved amino acid based on LTP gene sequence using these three model plants were designed. Polymerase chain reaction (PCR) amplification using these degenerate primers has resulted in amplification of various sizes of fragments, which are currently being cloned and sequenced. All products are subsequently characterized and compared using BLAST in NCBI. The result showed similarity about 100% with O. sativa, 68% with Sorghum bicolor, 66% with Z. mays, and 64% with Zea diploperennis,. Interestingly, we found that the expression of Elaies guineensis Lipid transfer protein (EgLTP) gene measured using Real-Time PCR showed that the expression level of EgLTP in infected oil palm was temporally down regulated. The results suggest that, down regulation of the EgLTP is related to the establishment of infection by Ganoderma boninense.